Numerical analysis of the effect of double-skin façade types on fire behaviour - Mehmet Akif Yıldız; Merve Ertosun Yıldız (Građevinar)
This study investigated the fire safety effect of double-skin façade (DSF) types that vary according to natural airflow through a numerical model. According to the cavity design, four DSF systems-multi-storey, corridor type, shaft type, and window-box type-were applied in the designed three-storey prototype office building, with the smoke spread based on fire and temperature levels analysed through simulation. Multi-storey and shaft-type DSF designs, which create a continuous cavity in the vertical direction, involve considering the chimney effect. In all the DSF designs, the office temperature did not reach the risk levels in the scenarios. By contrast, designs with a reduced cavity volume associated with the fire room caused the ambient temperature to increase.